Elaboração de modelo-ficha de patrimônios históricos a preservar : levantamentos técnicos e abordagens histórico-socioculturais - Fensterseifer, Margit Arnold (My University, 2016)
This research for the Professional Masters in History aims to methodologically formulate a record model for the complete description of buildings to be preserved for its history and socio-cultural importance in the communities they belong to. This record of architectural and historical indicators is a form model that is the resulting product of the study performed. In order to formulate the model-form, concepts such as memory, identity and culture were analyzed. Conceptualizing, also, in an appropriate way, terms such as tangible and intangible heritage, and analyzing the existing report models, it was possible to develop a more coherent and convincing record model, which will assist in data records for the preservation of buildings of historical importance. The explanation of these concepts complements the undergraduate studies for architects and urban planners, who have a superficial knowledge in this area. The model-form, once formatted, was presented to four Municipal Councils of Architectural Heritage and Cultural History. Then, it was validated by the present members of the councils. This material will guide the professional architects, urban planners and historians that take part in the councils to produce dimensional and photographic materials and detailed surveys of real estate and urban centers, in order to add the immaterial history to inventoried buildings, that can be preserved. For practical application and testing of the parameters, the case study of the village KM2 was analyzed. KM2 is an urban ensemble that was deployed by the railway battalion of Bento Gonçalves, on the border of the railroad. This local was chosen because it was a small social nucleus with its own life, independent from Bento Gonçalves (belonging to the line of Matos Verissimo). There occurred social, work and trade activities – and there also lived a different community that even today remember these periods of great happiness. Thus, under the direct observation of this community, it was possible to test the indicators, understanding how necessary it is to investigate and treat other historical buildings, being despised by communities, that end up deteriorating and being demolished. The act of preserving also need to go through the educational process and certainly the superior heritage education for architects and urban planners with a view to the near future, which will require these professionals to know, in depth, early history, preservation and restoration. Complement the proposed study for the Professional Masters in History the reflective analysis on the experience gained through contacts with the four municipalities councils and also the survey obtained through visits to four municipal councils. The record model to be filled with historical value of real estate will bring new guidelines to tell the stories of the cities, hidden in the past of the walls of these buildings.
Essa pesquisa para o Mestrado Profissional em História tem como objetivo formular metodologicamente um modelo-ficha para a descrição detalhada de edificações com potencial para preservação por sua história e sua importância sociocultural nas comunidades a que pertencem. Esse registro de indicadores arquitetônicos e históricos é um modelo de ficha, que consiste no produto resultante do estudo realizado. Com o intuito de formular esse modelo-ficha, foram analisados conceitos como memória, identidade e cultura. Conceituando, também, de forma adequada, termos como patrimônio material e imaterial, e analisando os modelos existentes de fichamento foi possível desenvolver um modelo-ficha mais coerente e convincente, que auxiliará nos registros dos dados para a preservação de edificações com importância histórica. A explanação desses conceitos complementa os estudos de graduação para os arquitetos e urbanistas, que possuem uma formação superficial nessa área de conhecimento. O modelo-ficha, depois de formatado, foi apresentado a quatro Conselhos Municipais de Patrimônio Arquitetônico Histórico e Cultural (COMPAHC), onde foi validado pelos membros neles presentes. Esse material orientará os profissionais arquitetos e urbanistas e historiadores participantes dos conselhos a produzir materiais e levantamentos dimensionais e fotográficos detalhados dos imóveis e conjuntos urbanos, de forma a agregar a história imaterial às edificações inventariadas e passíveis de tombamento. Para aplicação prática e para teste dos parâmetros indicados, foi realizado o estudo de caso da Vila KM2, conjunto urbano que consiste em um local implantado pelo batalhão ferroviário de Bento Gonçalves, às margens da via férrea. O espaço foi escolhido por ter sido um pequeno núcleo social com vida própria, independente do centro de Bento Gonçalves (pertencente à linha de Veríssimo de Matos). Ali aconteceram atividades sociais, de trabalho, de comércio e onde residiu uma comunidade diferenciada que até hoje lembra com saudades períodos de muita felicidade. Assim, sob a observação direcionada a esse grupo, foi possível realizar a experimentação dos indicadores, compreendendo como é necessário investigar e tratar os outros patrimônios que, sendo desprezados pelas comunidades, acabam se deteriorando e sendo demolidos. O ato de preservar também precisa passar pelos processos educativos e, certamente, pela educação patrimonial superior para arquitetos e urbanistas, com vistas a um futuro próximo, que exigirá desses profissionais conhecer, de modo aprofundado, princípios de história, preservação e restauro. Complementam o estudo proposto para o Mestrado Profissional em História a análise reflexiva sobre a experiência obtida por meio de contatos com conselhos dos quatro municípios e, também, o levantamento obtido por meio de visitas aos conselhos de quatro municípios. O modelo-ficha a ser preenchido com imóveis de valor histórico trará novas diretrizes para que sejam contadas as histórias dos municípios, escondidas nas paredes de edificações passadas.
Keywords: Patrimônio histórico - Conservação e restauração; Memória coletiva; Cidades e vilas; Historical heritage - Conservation and restoration; Collective memory; Cities and towns